Book Reviews. Issue 3 (1st December 2019) - Miller, Ray; Warfield, Scott; Thornton, Annette; Villarreal, Amanda Rose
What the Eye Hears: A History of Tap Dancing, Brian Seibert (2015)New York: Farrar, Straus and Giroux, 624 pp., ISBN 978-0-86547-953-1, h/bk, $35.00America Dancing: From the Cakewalk to the Moonwalk, Megan Pugh (2015)New Haven: Yale University Press, 416 pp., ISBN 978-0-30020-131-4, h/bk, $32.50The Complete Lyrics of Alan Jay Lerner, Dominic McHugh and Amy Asch (eds) (2018)New York: Oxford University Press, xxiv+607 pp., ISBN 978-0-19064-673-8, h/bk, £32.99/$44.95When Broadway Went to Hollywood, Ethan Mordden (2016)New York: Oxford University Press, 325 pp., ISBN 978-0-190939-540-8, h/bk, £19.99Building Character: The Art and Science of Casting, Amy Cook (2018)Ann Arbor: University of Michigan Press, 188 pp., ISBN 978-0-47205-376-6, h/bk, $65.00, p/bk, $24.95